Food for thought: Edible gardens in New Zealand primary and secondary schools - Collins, C.; Richards, R.; Reeder, A. I.; Gray, A. R. (Health promotion journal of Australia, 2015)
Issue addressed: School gardens are a potentially important health promotion tool, allowing the growth and consumption of fruit and vegetables to be embedded within the students' educational experience. This study aimed to investigate the implementation of edible gardens in New Zealand (NZ) primary and secondary schools. Methods: A questionnaire mailed to principals from a randomly selected sample of 764 NZ schools included questions on whether or not the school had a garden and, if so, what produce was grown; how long the garden had been in place; how harvested crops were distributed; and curriculum integration. Results: Among 491 responding schools (64.3% response rate), 52.9% currently had an edible garden - with most gardens started in the previous two years. Vegetables, herbs and tree fruit were commonly grown. Gardens were integrated into curriculum subjects, cooking lessons, recipes and messages promoting increased fruit and vegetable consumption. Conclusions: Edible gardens were common within NZ schools, though often relatively new, and were used for teaching in a variety of curriculum areas.